Deep sedation vs femoral block anesthesia: beat-by-beat hemodynamic impact on TAVI procedure - Romano, Salvatore Mario (Am J Cardiovasc Dis, 2020)
Background: In spite of the increased use of Trans-catheter Aortic Valve Implantation (TAVI) due to the better patient selection, well-trained operators and improved technology, the choice of the best anesthesia regimen remains an open question. In particular, it remains to be clarified whether deep sedation (DS) in spontaneous breathing or femoral local anesthesia (LA) is best. Objective: This study compared the hemodynamic variations determined by deep sedation (DS) with spontaneous breathing and local femoral anesthesia (LA) in 2 groups of patients submitted to TAVI with two different kinds of anesthesia, using a beat-by-beat pulse contour method (MostCare(®-UP)). Methods: 82 patients with severe aortic stenosis and similar baseline characteristics and indications underwent trans-femoral TAVI: 50 with LA and 32 with DS. All patients were submitted to minimally invasive hemodynamic monitoring. The following parameters were measured: pressure indexes: systolic, diastolic, mean (SysP, DiaP, MAP) and dicrotic (DicP) pressures; flow indexes: cardiac output (CO), stroke volume (SV); ventriculo-arterial coupling indexes (VAC): peripheral arterial elastance (Ea(P)), systemic vascular resistance (SVR); cardiovascular system performance: cardiac cycle efficiency (CCE), dP/dt(max_rad). Results: The TAVI procedure was successful in 89% of patients (VARC-2 criteria) with no difference between the 2 groups. Anesthesia induction determined a higher decrease of pressures in DS than in LA (P<0.01) with no differences in CO. The VAC parameters (Ea(P), SVR) decreased (P<0.01) in DS with an improvement in CCE (P<0.001); these parameters did not change in LA. The post-TAVI flow and VAC parameters, especially Ea, increased (P<0.05) more significantly in the LA group than in the DS group (P<0.001). Using logistic regression, the occurrence of the post-TAVI aortic regurgitation was correctly associated with the pressure gradient MAP-DicP in 63% of the study population (P=0.033). This association was more effectively detected in the LA group (78%, P=0.011) with a ROC AUC=0.779, than the DS group. Conclusion: The use of the pulse contour method to track the fast-hemodynamic changes during the TAVI procedure proved suitable for the aim. As expected, LA and DS induced different pre-TAVI hemodynamic conditions, which influenced the post-TAVI hemodynamic changes. The hemodynamic conditions induced by LA, enabled the occurrence of post-TAVI aortic regurgitation to be detected more effectively.